A preliminary study of Hello Barbie in Brazil and Argentina. (July 2018) - Fantinato, Marcelo; Hung, Patrick C.K.; Jiang, Ying; Roa, Jorge; Villarreal, Pablo; Melaisi, Mohammed; Amancio, Fernanda
Abstract: A smart city is an urban development vision based on Information and Communication Technology (ICT) and the Internet of things (IoT) for the city's management and operations. The smart city concept is raised simultaneously in many modern societies. IoT is always playing an important role as smart devices to support complex scenarios in smart cities. A smart toy, such as "Hello Barbie, " is a smart device consisting of a physical toy component that connects to a computing system with online services through networking to enhance the functionality of a traditional toy. In this research, we particularly studied Brazilian and Argentinian consumers' perceived innovativeness, risks and benefits of smart toys and their purchase intention toward such toys. Results indicate that Brazilian consumers have better perception and evaluation of the toy and thus higher purchase intention than Argentinian consumers do. Such difference may be explained by the cultural differences between the two countries, such as relatively low vs. high uncertainty avoidance. We also provide our recommendations for smart toys manufacturers to address these issues for the future products.